MENGATASI KESULITAN BELAJAR DENGAN PENDEKATAN PSIKOLOGI KOGNITIF - Ridwan Idris (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2009)
The profession of teaching is not always easy, as it needs respective knowledge and skill. The responsibility of teachers is not only to transfer their knowledge to their students, but most importantly is to help them solve learning difficulties. Students coming to schools bring different problems as they are from different background. Some go to school with their personal problems, and some with family problems. The teachers, therefore, should be close to their students and know their individual learning difficulties, and help them how to learn effectively.